2022
DOI: 10.3389/fmed.2021.600107
|View full text |Cite
|
Sign up to set email alerts
|

Women's COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is no longer a respiratory disease that predominantly affects men, to the point where the prevalence among women has equaled that of men since 2008, partly due to their increasing exposure to tobacco and to biomass fuels. Indeed, COPD has become the leading cause of death in women in the USA. A higher susceptibility of female to smoking and pollutants could explain this phenomenon. Besides, the clinical presentation appears different among women with more frequent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Similarly, expression of NLRX1 was reduced in aneurysm-induced brain injury ( 27 ) and in chronic obstructive pulmonary disease (COPD) ( 110 ). Interestingly, in COPD, disease prevalence does not seem to differ between men and women, however the clinical presentation is different and more severe in women ( 111 ). Whether NLRX1 contributes to sex differences observed in these pathologies remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, expression of NLRX1 was reduced in aneurysm-induced brain injury ( 27 ) and in chronic obstructive pulmonary disease (COPD) ( 110 ). Interestingly, in COPD, disease prevalence does not seem to differ between men and women, however the clinical presentation is different and more severe in women ( 111 ). Whether NLRX1 contributes to sex differences observed in these pathologies remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This skewed gender representation is casual but should be considered, since it might affect the results. For example, COPD manifestations differ between males and females with the latter being more at risk of developing severe disease [ 22 ]; similarly respiratory impairment in FRDA might impact differently in the two genders, however this will require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last years of the study period, females had a higher percentage of hospitalizations due to chronic lower respiratory diseases compared to males. Recent data from the literature show an increase in the incidence of COPD among females and that COPD is no longer a disease of males [ 51 ]. In addition, previous studies in the UK showed that the rates of admissions due to chronic lower respiratory diseases in the UK were higher among females compared to males [ 50 , 52 ], which was consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Females tend to be more susceptible to smoking. In addition, females tend to have a longer life expectancy, which puts them at a higher risk of developing chronic lung diseases [ 51 ]. These factors may explain the increase in the rate of hospitalization due to chronic lower respiratory diseases among females compared to males.…”
Section: Discussionmentioning
confidence: 99%